RELIGIUSITY, PROMOTION AND LIFESTYLE ON STUDENTS CONSUMTIVE BEHAVIOR IN ONLINE SHOPPING - Dienillah, Izzah; Rofi’illah, Ahmad Hendra; Raharto, Eko (LAN TABUR: Jurnal Ekonomi Syariah The Islamic University of KH. Achmad Muzakki Syah Jember, East Java. Jember Jln. Manggar Gebang Poreng 139A Patrang Jember Jawa Timur, 2024)
The development of the times makes people consume goods and services not only based on needs but also the desire for self-satisfaction, thus causing someone to behave consumptively. A consumer's behavior should reflect his or her religiosity to Allah SWT. But with promotions, people often neglect shopping. Apart from that, today's teenagers consider that hedonic behavior is a lifestyle that has its appeal for teenagers. This research aims to determine the influence of lifestyle, religiosity, and promotion on students' consumptive behavior in online shopping. This type of research is descriptive using a quantitative approach, sampling uses the Simple Random Sampling method and the data collection technique uses a questionnaire with respondents as many as 52 students. Hypothesis analysis uses multiple linear regression analysis. Based on the results of research that has been conducted, show that religiosity does not influence students' consumptive behavior in online shopping. The promotion and lifestyle variables have a significant effect on students' consumptive behavior in online shopping.